Involvement of chemerin and CMKLR1 in the progesterone decrease by PCOS granulosa cells. Issue 6 (28th October 2021) - Estienne, Anthony; Mellouk, Namya; Bongrani, Alice; Plotton, Ingrid; Langer, Ingrid; Ramé, Christelle; Petit, Claire; Guérif, Fabrice; Froment, Pascal; Dupont, Joëlle
Abstract : Polycystic ovarian syndrome (PCOS) is the main cause of infertility in women. It is frequently associated with reduced progesterone production by human luteinised granulosa cells (hlGCs). However, the molecular mechanisms involved in these steroidogenesis alterations in PCOS patients are unclear. In a dihydrotestosterone-induced PCOS mouse model, steroid production is maintained in the setting of chemokine-like receptor 1 ( Cmklr1 ) knockout. Thus, chemerin and chemerin receptors in terms of expression and progesterone regulation could be different in control and PCOS hlGCs. We first confirmed that progesterone levels in both plasma ( P   < 0.0001) and follicular fluid (FF) ( P   < 0.0001) were significantly reduced in PCOS normal weight women compared to control women. These data were associated with a lower STAR mRNA expression in both in vivo ( P   < 0.0001) and in vitro ( P   < 0.0001) hlGCs from PCOS women. Secondly, chemerin FF levels ( P   < 0.0001) and RARRES2 ( P   < 0.05) and CMKLR1 ( P   < 0.0001) mRNA levels in GCs were higher in PCOS normal weight patients. Thirdly, treatment of hlGCs with a specific nanobody (the VHH CA4910) targeting the human receptor for CMKLR1 leading to its inactivation abolished chemerin-induced progesterone inhibition, suggesting the involvement of CMKLR1 in this process. Furthermore, the inhibition of progesterone secretion induced by chemerin was two-fold higher in PCOS hlGCs ( P   < 0.05). Moreover, the VHH CA4910 reinstated a normal progesterone secretion with lower concentrations in PCOS hlGCs, suggesting a different chemerin sensitivity between PCOS and control hlGCs. Thus, chemerin, through CMKLR1, could be involved in the steroidogenesis alterations in PCOS hlGCs.